Essays on social choice and implementation theory - SALLES RAMOS, Paulo Daniel (Institutional Knowledge at Singapore Management University, 2022)
We present here three essays. The first two are about Social Choice Theory and explore under what domain restrictions is possible to obtain a Social Choice Function that is Well Behaved as well as Monotonic, and what other characteristics can be inferred about such functions on that domain. The last essay is about Implementation Theory and explore how to obtain a more compelling form of implementation than pure Nash Equilibrium for finite environments using finite mechanisms.